Experimental investigation of orientation effect on flow boiling heat transfer performance of R134a refrigerant in minichannels - Wong, Isaac Kai Hunn (Nanyang Technological University, 2024)
Two-phase cooling takes into consideration various practical designs of minichannels to enhance flow boiling performance and increase heat dissipation. A significant number of previous studies have primarily focused on the benefits of open micro/minichannel designs for horizontal orientation flow boiling. However, these approaches often result in a lack of understanding of the effects of orientation on flow boiling and heat dissipation in closed and opened channels. Due to the large density difference of the coolant’s liquid and vapour phase, the flow channel orientation can have significant effect on the two-phase flow pattern and heat transfer performance. This project advances beyond previous studies through flow boiling experimental characterization of parallel minichannels in horizontal and vertical orientation. In the horizontal orientation, minnichannels are upward facing where in the vertical orientation, the coolant flow in along and against the direction of gravity are investigated. Experiments were conducted under steady-state condition and at a constant mass flow rate of 0.005 kg/s. R134a was used as the working fluid flowing through the cold plate with closed (0 mm) and open (0.5 mm and 1 mm manifold gap) minichannels with uniform solid fins with a width of 2mm. Each parallel minichannel had dimensions of 2 mm channel spacing width and 1 mm height depth. The boiling performance of the sample was evaluated under heat fluxes varying from 79.52 to 930.17 kW/m2, with a mass flux maintained at 73 kg/m2·s and an inlet sub-cooling temperature set at 2°C. Throughout the experiment, various parameters were documented, including the average wall temperature, critical heat flux (CHF), heat transfer coefficient, and pressure drop. Additionally, a high-speed camera was utilized to capture the flow patterns occurring within the cold plates. In horizontal orientation, the open manifold gap provided additional space for the expansion of bubbles to mitigate flow instabilities. However, in the vertical orientations, the manifold gap led to various issues including vapour slug coalescence, elongation, and stagnation which led to dry-out and lower cooling performances. The experimental results concluded that the open-channel plate with a 0.5 mm manifold gap had a significantly better cooling performance in horizontal orientation with a wall superheated temperature 26% lower than and heat transfer coefficient 15% and 38% higher than cold plate with 0 mm and 1 mm manifold gaps in the high heat flux region. However, the 0 mm manifold gap performed better in vertical upward orientation with heat transfer coefficients that are 45% and 19% higher than the 0.5 mm and 1 mm manifold gaps, respectively in the high heat flux region. Similarly, the 0 mm manifold cold plate performed better in vertical downward orientation, with heat transfer coefficients that are 30% and 94% higher as compared to the 0.5 mm and 1 mm manifold gaps, respectively.